2009
DOI: 10.3991/ijim.v4i1.1086
|View full text |Cite
|
Sign up to set email alerts
|

Advanced and Effective Learning in Context Aware and Adaptive Mobile Learning Scenarios

Abstract: The ability to support students/learners to learn on the move at any place and at any time is new task to be addressed by using the mobile devices of the learners. Mobile technology support has given birth to the concept of mobile learning possessing a wide spectrum of applications and new teaching and learning techniques. This paper discusses a study conducted for undergraduate students on the effect of mobile technology usage in a learning process. The results showcased here indicate acceptance of the mobile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The expert validation result showed that the product developed in this research, the Rawa Danau Nature Reserve website, has possibilities for use as an online learning source to support conservation education. The implementation of website-based learning can increase the student cognition [37] and the enthusiasm of both teacher and students as well [38]. In addition, web-based learning is an alternative to traditional pedagogical approaches and learning techniques that can be appropriate to students' psychological needs and can allow collaboration, stimulate creativity, and enable analytical thinking for solving problems [39].…”
Section: Fig 7 Results Of the Gt-metrix Testmentioning
confidence: 99%
“…The expert validation result showed that the product developed in this research, the Rawa Danau Nature Reserve website, has possibilities for use as an online learning source to support conservation education. The implementation of website-based learning can increase the student cognition [37] and the enthusiasm of both teacher and students as well [38]. In addition, web-based learning is an alternative to traditional pedagogical approaches and learning techniques that can be appropriate to students' psychological needs and can allow collaboration, stimulate creativity, and enable analytical thinking for solving problems [39].…”
Section: Fig 7 Results Of the Gt-metrix Testmentioning
confidence: 99%
“…Such factors may include location, time, physical surroundings, network and computing characteristics, users' preferences. A set of mechanisms supporting context adaptation in m-learning was presented by a group of researchers (Bhaskar & Govindarajulu, 2008;Economides, 2009;Elhamdaoui et al, 2011). In which, the learning context was described in a set of dimensions including; the mobile device, the network, learner and the environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the reported uses of m-learning are: to enhance the user experience in visitors of an art museum, to take advantage of the learning context [3], to allow students to participate on an academic discussion forum [4], in training for personnel in disaster or emergency situations [5], to suggest didactic methods that are adequate to a specific teaching situation [6], and in the learning of science [7], languages [8], and medicine [9].…”
Section: Mobile Learningmentioning
confidence: 99%